Multi‐centre randomised trial of invasive and less invasive surfactant delivery methods showed similar spirometry results at 5–9 years of age. (9th August 2022) - Göpel, Wolfgang; Kribs, Angela; Roll, Claudia; Wieg, Christian; Teig, Norbert; Hoehn, Thomas; Welzing, Lars; Vochem, Matthias; Hoppenz, Marc; Bührer, Christoph; Mehler, Katrin; Hubert, Mechthild; et al.
Abstract: Aim: We explored whether subnormal forced expiratory volume within 1 s (FEV1 ) at 5–9 years of age was lower in children born preterm who received less invasive surfactant administration (LISA) rather than surfactant via an endotracheal tube. Methods: The multi‐centre, randomised Nonintubated Surfactant Application trial enrolled 211 preterm infants born at 23–26 weeks of gestation from 13 level III neonatal intensive care units from April 2009 to March 2012. They received surfactant via LISA ( n  = 107) or after conventional endotracheal intubation ( n  = 104). The follow‐up assessments were carried out by a single team blinded to the group assignments. The main outcome was FEV1  < 80% of predicted values. Results: Spirometry was successful in 102/121 children. The other children died or were lost to follow‐up. Median FEV1 was 93% (interquartile range 80%–113%) of predicted values in the LISA group and 86% (interquartile range 77–102%) in the control group ( p  = 0.685). Rates of FEV1  < 80% were 11/57 (19%) and 15/45 (33%), respectively, which was an absolute risk reduction of 14% (95% confidence interval −3.1% to 31.2%, p  = 0.235). There were no differences in other outcome measures. Conclusion: The proportion of children aged 5–9 years with subnormal FEV1 was not significantly different between the groups.